Why can’t MENA countries trade more?: The curse of bad institutions - Karam, Fida; Zaki, Chahir (International Food Policy Research Institute, 2017)
This paper explores the relationship between institutions and trade in the Middle East and North Africa (MENA) region. The literature offers a broad consensus that bad institutions hamper trade and that trade liberalization engenders institutional reforms; however, MENA has generally been neglected in this literature, even though most countries in the region suffer from a clear deficit of “good” institutions. Taking into account the inverse relationship between institutions and trade, we use a gravity model that explains bilateral trade for disaggregated goods and service sectors for 21 MENA countries over the period 1995-2014. Our results show that in the presence of excessive zero trade observations, poor institutions can be considered as fixed export costs that help explain the zero probability of trade for some countries. We find that institutions do matter for trade after controlling for the endogeneity problem between institutions and trade.